2019
DOI: 10.1017/s1365100519000336
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Public Debt and Inequality in a General Equilibrium Model

Abstract: This study investigates the relationship between the sustainability of public debt and inequality in an endogenous growth model with heterogeneous agents. We show that the threshold for the sustainability of public debt is related to not only the relative size of public debt but also inequality. In addition, this study examines the effects of budget deficit and redistributive policies on the sustainability of public debt and inequality. We show that an increase in the deficit ratio or the redistributive tax ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…The study found that non-Latin American economies are considered resilient in the short term, as their debt remains below thresholds of 40%-55% of GDP, while financial resilience is a much more challenging task for most Latin American economies due to their debt accumulation above the threshold, representing about 35% of GDP, which is relatively lower than projected for other countries (Tran, 2018). Maebayashi and Konishi (2019) examined the relationship between public debt sustainability and inequality in an endogenous growth model with heterogeneous agents, and the impact of fiscal deficits and redistributive policies on public debt sustainability and inequality. The researchers concluded that the threshold for public debt sustainability is related not only to the relative size of public debt but also to inequality.…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…The study found that non-Latin American economies are considered resilient in the short term, as their debt remains below thresholds of 40%-55% of GDP, while financial resilience is a much more challenging task for most Latin American economies due to their debt accumulation above the threshold, representing about 35% of GDP, which is relatively lower than projected for other countries (Tran, 2018). Maebayashi and Konishi (2019) examined the relationship between public debt sustainability and inequality in an endogenous growth model with heterogeneous agents, and the impact of fiscal deficits and redistributive policies on public debt sustainability and inequality. The researchers concluded that the threshold for public debt sustainability is related not only to the relative size of public debt but also to inequality.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Maebayashi and Konishi (2019) examined the relationship between public debt sustainability and inequality in an endogenous growth model with heterogeneous agents, and the impact of fiscal deficits and redistributive policies on public debt sustainability and inequality. The researchers concluded that the threshold for public debt sustainability is related not only to the relative size of public debt but also to inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The above studies suggest that the government should conduct fiscal policy from a long-run perspective. 1 However, except for Borissov and Kalk [ 10 ] and Maebayashi and Konishi [ 23 ], few theoretical studies have examined the effects of public debt on income inequality. In recent years, empirical studies have reported a positive correlation between income inequality and public debt (e.g., Azzimonti et al [ 2 ]; Bartak et al [ 5 ]; Luo [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%
“…IMF [27] describes debt sustainability as the need to satisfy solvency condition without subject to correction or additional cost of financing. To further highlight the importance of debt sustainability, some studies claimed that such solvency condition must ensure that public debt plus the discount value of entirely government spending does not exceed the present value of generated revenues of non-interest spending [14,32].…”
Section: Introductionmentioning
confidence: 99%